PENGARUH STRESS KERJA TERHADAP KINERJA PERAWAT RUANG INAP KELAS II DAN III PADA RUMAH SAKIT UMUM DAERAH (RSUD) ARIFIN ACHMAD PROVINSI RIAU - Dwi Septi; Jumiati Sasmita; Raden Lestari Ganarsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The hospital is one form of health facilities, both organized by the government and or the community. The success of a hospital in its function characterized by an increase in the quality of hospital services. Hospital quality so obtained by several factors. The most dominant factor is resource. The purpose of this study was to determine the effect of work stress on the performance of nurse -patient room class II and III on General Hospital (Hospital) Arifin Achmad Riau Province. The population of nurses around the hospital room class II and III who served in the last year ie in 2010 on General Hospital (Hospital) Arifin Achmad Riau province, as many as 216 people with a sampling of 68 people by using cluster sampling. The technique of collecting data through questionnaires were analyzed quantitatively. T-test results prove that there is a significant effect of work stress on the performance of nurse-patient room class II and III on General Hospital (Hospital) Arifin Achmad Riau inversely proportional to the nature of the effect. What this means is that the higher the stress level of nurses, the nurse's performance will decrease. It was determined that the effect of work stress on the performance of nurse-patient room class II and III on General Hospital (Hospital) Arifin Achmad Riau Province amounted to 41.8%. While the rest are not influenced by other variables studied.Keywords : Job Stress And Employee Performance